The analysis of possible ways of the destruction of Boko Haram radical islamist activities on families in North -Eastern Nigeria - Bature, A. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
The vicious cycle of Boko Haram attacks in Nigeria since 2009 tend to have created worst ever security situation since independence in 1960. This paper examined psychological effects of Boko Haram activities on families in the North Eastern Nigeria. It argued that the devastating impacts of Boko Haram activities on families in the North East will likely inculcate revulsion among the people and religious organizations. The paper observed that the disillusionment arising from such distaste perhaps will sustain a long period of insecurity even if Boko Haram is defeated in the nearest future. It observed that in spite of efforts made so far by government agencies, government needs to redouble her efforts to reduce hardship arising from the present insecurity in the North East as a measure to tackle psychological impacts of insecurity. The study adopted qualitative descriptive analytical methods and relied on the social bond theory as its theoretical compass. It recommended among others a paradigm shift from the hitherto government poor approaches to solving problems of national importance to a more responsive strategy, sufficient enough to counter or rather address the security crisis in the North Eastern Nigeria. Key words: Psyhological attacks, Boko Haram, devasting impacts, islam, paradigm shift, responsive strategy.